Empowering of agricultural extensionists: a case study of frontline extensionists of one agricultural extension agency - M. Sail, Rahim (Centre for Extension, Entrepreneurship and Professional Advancement (APEEC), Universiti Putra Malaysia, 2010)
The main purpose of the study is to determine the importance of job empowerment in extension work as well as to determine the level of knowledge and skill in agriculture, management of an enterprise and human resource development (HRD). The study employed a survey design using questionnaire developed by the researcher to measure the criterion and predictor variables. The findings indicated that about one-half (48%) of the respondents perceived that job empowerment was “not important” and “somewhat important” in their jobs. Similar findings with almost similar percentages were recorded for all the predictor variables. These findings clearly indicate that the lack of exposure and understanding among agricultural extensionists on the concept and practice of job empowerment, especially on how job empowerment would enhance the effectiveness of their extension work. Agricultural extensionists should be trained on the concept and practice of job empowerment focusing on the visible(technical and management knowledge) as well as the hidden(motives, traits, self-concept) aspects of individual competencies to develop superior performance.